IMPLEMENTASI KEBIJAKAN PERATURAN GUBERNUR JAWA TENGAH NOMOR 51 TAHUN 2020 TENTANG TAMBAHAN PENGHASILAN KEPADA PEGAWAI NEGERI SIPIL DI SMK NEGERI 1 JATI - Sutrisno Sutrisno (Master of Public Administration, Universitas Slamet Riyadi, 2022)
This study aims to analyze the implementation of the Additional Income Policy forCivil Servants in the province of Central Java. The research method uses qualitativeresearch with descriptive methods. Data collection techniques include interviews,observation, and documentation. Informants were selected based on purposivesampling. The analysis of the implementation of the Edward III model shows that,1) Communication, socialization has not been maximized, because it is onlyattended by a limited number of people. 2) Resources, from the aspect of quantityof human resources, funding and infrastructure are not sufficient. 3) Dispositionwhich includes honesty, discipline and commitment has been carried out well. 4)the bureaucratic structure that is related to the main tasks and functions has beengoing wellKeywords: implementation, communication, resources, disposition, bureaucracy